Special Award for Mandarin For All - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 7 November – Mandarin for All published by Penerbit UMP has won the gold medal and special award in British Invention Show in London recently. Written by Yong Ying Mei, a language teacher at the Centre of Modern Language and Human Sciences, this book has been equip with QR code for audio aiming at preparing the learners for Hanyu Shuiping Kaoshi test.